Shaping particles by chemical diffusion and reaction. Issue 1 (30th November 2016) - Yang, Tao; Liu, Jianmei; Dai, Jinhui; Han, Yongsheng
Abstract : Three growth modes of particles are proposed based on the difference in chemical diffusion and reaction rates, which is examined in this paper. Abstract : Here, we report a general role of chemical diffusion and reaction in shaping particles. It is supposed that chemical diffusion and reaction play a role in shaping particles by changing the chemical distribution around the growth front of particles. Based on this understanding, three growth modes of particles are proposed in this paper, namely, reaction-limited mode, diffusion-limited mode, and reaction–diffusion balance mode. Silver particles are synthesized in different growth modes by various methods. No matter which method is employed, silver particles synthesized in the same mode have similar morphologies. To further generalize diffusion and reaction effects, copper and gold particles are synthesized. The morphological evolution of these two types of particles is similar to that of silver. These results indicate the general role of chemical diffusion and reaction in shaping particles, promising that a regulation on these two kinetic factors is a green and powerful technique for rational synthesis of materials.